Effects of Temperature and Light on Microalgal Growth and Nutrient Removal in Turtle Aquaculture Wastewater - Xiaosong Tian; Xiaoai Lin; Qing Xie; Jinping Liu; Longzao Luo (Biology)
The aim of this study was to explore the effects of temperature and light on microalgal growth and nutrient removal in turtle aquaculture wastewater using a single-factor experiment method. Results showed that the growth process of Desmodesmus sp. CHX1 in turtle aquaculture wastewater exhibited three stages, namely adaptation, logarithmic, and stable periods. Temperature and light significantly influenced the growth and protein and lipid accumulation of Desmodesmus sp. CHX1. The optimal conditions for the growth and biomass accumulation of Desmodesmus sp. CHX1 included a temperature of 30 °C, a photoperiod of 24L:0D, and a light intensity of 180 μmol photon/(m2·s). Increased temperature, photoperiod, and light intensity enhanced nutrient removal efficiency. Maximum nitrogen removal was achieved at a temperature of 30 °C, a photoperiod of 24L:0D, and a light intensity of 180 μmol photon/(m2·s), with the removal efficiency of 86.53%, 97.94%, 99.57%, and 99.15% for ammonia, nitrate, nitrite, and total phosphorus (TP), respectively. Temperature did not significantly affect TP removal, but increased photoperiod and light intensity improved the removal efficiency of TP. The development of microalgae biomass as a feed rich in protein and lipids could address feed shortages and meet the nutritional needs of turtles, offering a feasible solution for large-scale production.